Pengaruh Penerapan Corporate Social Responsibility (CSR) terhadap Nilai Perusahaan - Aidil Putra Pratama; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2024)
The aim of this research is to examine the impact of implementation of Corporate Social Responsibility (CSR) on the firm value of logistics and transportation companies listed on the Indonesia Stock Exchange (IDX) 2018 - 2022. This study used simple linear regression method by using SPSS. This research sample used a purposive sampling technique, from the 37 companies used as the population, 19 companies were obtained as samples. The results showed that Corporate Social Responsibility (CSR) disclosure affects firm value (Tobin’s Q). Furthermore, Robustness Test in this study result showed that Corporate Social Responsibility (CSR) effects on firm value if measured by Net Profit Margin (NPM).